PHA production by mixed cultures: A way to valorize wastes from pulp industry - Queiros, Diogo
In this work, hardwood spent sulfite liquor (HSSL), a complex feedstock originating from the pulp industry, was tested for the first time as a substrate for polyhydroxyalkanoate (PHA) production by a mixed microbial culture (MMC) under aerobic dynamic feeding (ADF) conditions. A sequencing batch reactor (SBR) fed with HSSL was operated for 67 days and the selected MMC reached a maximum PHA content of 67.6%. The MMC demonstrated a differential utilization of the carbon sources present in HSSL. Acetic acid was fully consumed, while xylose and lignosulphonates were partially consumed (30% and 14%, respectively). The selected culture was characterized by Fluorescence in Situ Hybridization (FISH). Bacteria belonging to the three main classes were identified: Alpha-(72.7 +/- 4.0%), Beta-(11.1 +/- 0.37%) and Gammaproteobacteria (10.3 +/- 0.3%). Within Alphaproteobacteria, a small amount of Paracoccus (4.2 +/- 0.51%) and Defluvicoccus related to Tetrad Forming Organisms (9.0 +/- 0.28%) were detected. (C) 2014 Elsevier Ltd. All rights reserved.